Crosslinked Remote‐Doped Hole‐Extracting Contacts Enhance Stability under Accelerated Lifetime Testing in Perovskite Solar Cells. Issue 14 (29th January 2016) - Xu, Jixian; Voznyy, Oleksandr; Comin, Riccardo; Gong, Xiwen; Walters, Grant; Liu, Min; Kanjanaboos, Pongsakorn; Lan, Xinzheng; Sargent, Edward H.
Abstract : A crosslinked hole‐extracting electrical contact is reported, which simultaneously improves the stability and lowers the hysteresis of perovskite solar cells. Polymerizable monomers and crosslinking processes are developed to obviate in situ degradation of the under lying perovskite. The crosslinked material is band‐aligned with perovskite. The required free carrier density is induced by a high‐work‐function metal oxide layer atop the device, following a remote‐doping strategy.